Coupling photo-, mechano- and thermochromism and single-ion-magnetism of two mononuclear dysprosium–anthracene–phosphonate complexes. Issue 26 (14th March 2018) - Huang, Xin-Da; Kurmoo, Mohamedally; Bao, Song-Song; Fan, Kun; Xu, Yan; Hu, Zhao-Bo; Zheng, Li-Min
Abstract : Dy III (depma)3 (NO3 )3 (1 ) and Dy III (depma)4 (NO3 )2 (CF3 SO3 ) (2 ) with different supramolecular interactions between anthracene moieties show single-ion-magnetism coupled to photo- and mechanochromism that are partially reversible by thermal annealing. Abstract : Dy III (depma)3 (NO3 )3 (1 ) and Dy III (depma)4 (NO3 )2 (CF3 SO3 ) (2 ) differ structurally by the number of depma ligands and the supramolecular interactions (π–π and C–H⋯π, respectively) between anthracene moieties. They exhibit single-ion-magnetism which is coupled to photo- and mechanochromism that are partially reversible by thermal annealing. The changes are associated with the formation and destruction of excimers.